2009
DOI: 10.1186/1471-2164-10-419
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of microRNA and mRNA profiles in neuronal development and synapse formation

Abstract: Background: Synapse formation and the development of neural networks are known to be controlled by a coordinated program of mRNA synthesis. microRNAs are now recognized to be important regulators of mRNA translation and stability in a wide variety of organisms. While specific microRNAs are known to be involved in neural development, the extent to which global microRNA and mRNA profiles are coordinately regulated in neural development is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 66 publications
3
29
1
Order By: Relevance
“…In addition to the effects on absolute miRNA quantification, our findings also have implications for relative miRNA quantification strategies in which the relative expression of multiple miRNAs has been determined in comparison to each other or the same miRNAs in different experimental conditions, due to the significant uncertainty associated with the measurement of both experimental and housekeeping miRNAs. Indeed, previous studies have reported significant differences in relative miRNA expression of as low as 1.5-fold (41, 42), but our findings suggest that such small differences in expression should be treated with caution.…”
Section: Resultscontrasting
confidence: 51%
“…In addition to the effects on absolute miRNA quantification, our findings also have implications for relative miRNA quantification strategies in which the relative expression of multiple miRNAs has been determined in comparison to each other or the same miRNAs in different experimental conditions, due to the significant uncertainty associated with the measurement of both experimental and housekeeping miRNAs. Indeed, previous studies have reported significant differences in relative miRNA expression of as low as 1.5-fold (41, 42), but our findings suggest that such small differences in expression should be treated with caution.…”
Section: Resultscontrasting
confidence: 51%
“…Local translation-dependent synaptic LTD is tightly controlled by a number of different post-transcriptional mechanisms, such as the ubiquitin-proteasome system (Hou et al, 2006;Yashiro et al, 2009), translation initiation and elongation (Costa-Mattioli et al, 2005), and by microRNAs (miRNAs) (Manakov et al, 2009). MiRNAs are small, evolutionarily conserved signaling molecules that act as silencing regulators of mRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA control of gene expression has been implicated in developmental regulation and mature cell maintenance (Cheng et al, 2009; Christensen and Schratt, 2009; Fineberg et al, 2009; Harfe, 2005; Lau and Hudson, 2010; Manakov et al, 2009). In the nervous system, gross evaluation of total miRNA expression has been profiled, revealing strong miRNA enrichment in developing and mature neuronal tissue (Krichevsky et al, 2003; Krichevsky et al, 2006; Miska et al, 2004).…”
Section: Introductionmentioning
confidence: 99%